Use of narratives to assess language disorders in an inpatient pediatric psychiatric population. (April 2014) - Pearce, Patsy; Johnson, Carolyn; Manly, Patricia; Locke, Jake
A large proportion of child psychiatry patients have undiagnosed language disorders. Adequately developed language is critical for psychotherapy and cognitive-behavioral therapies. This study investigated (1) whether assessment of oral narratives would identify language impairments in this population undetected by assessment of only core language abilities, and (2) the extent to which measures of cognition, working memory, emotional distress, and social function differentially predict core language and narrative development. Results showed that (1) more than twice as many children were identified with language impairment when both narrative and core language assessment were used, and (2) core language comprehension and complex verbal working memory were the strongest predictors of narrative production, while core language comprehension, a less complex working-memory task, and social skills best predicted narrative comprehension. Emotional distress did not predict either. The results emphasize the importance of evaluating child psychiatry patients' language, using both core language and narrative measures.